RANCANGAN CONTINUOUS STIRRED TANK REACTOR UNTUK SINTESIS NANOPARTIKEL WO3 - Maya Lianawati; Asep Bayu Dani Nandiyanto; Meli Fiandini; Risti Ragadhita (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2023)
This research aim to develop a continuous stirred tank reactor (CSTR) in the meant to produce WO3 nanoparticles. A manual calculations was done using Microsoft Excel. The result obtained CSTR with a tank designed with volume 1301.14 m3 volume, height 1.26 m, and 1.19 designed hydrostatic pressure. The reactor also equipped with 1 stirrer with length 0.23 m and width 0.18 m. This study expected to be useful reference for production of WO3 nanoparticles in industrial scale.